Microstructure variation effects influence on characteristics and mechanical properties of Monel 400 and low alloy steel (ASTM 387-Gr.11) GTAW dissimilar joint - Abdulameer, Ahmed Ghazi; Mohammed, Mohammed Sabeeh; Abbas, Ahmed Salloum (Eastern-European Journal of Enterprise Technologies, 2022)
Monel 400 with low alloy steel dissimilar joints are widely used in oil industry, petrochemical and nuclear engineering, this kind of applications needs welding joints with good mechanical properties, stable magnetic permeability and good weldability. Difference in mechanical, chemical and physical properties between these unique alloys makes such joint difficult and joints mechanical properties and microstructure will be different from parent metals. In this study, GTAW process has been employed with ERNiCrFe-3 electrode to produce dissimilar welding joints with specifies welding procedure parameters, SEM/EDS microstructure analysis, microstructure optical test, Vickers microhardness and tensile test used to study microstructure details and its impacts on welding joint mechanical properties. Research results according to welding zone microstructure analyses shown formation of Widmanstatten ferrite structures and second phase particles with fine graine structure in low alloy steel side the formation of transion zone (TZ). Moreover, clearly fusion line (FL) clearly marked in Monel 400 side while weld metal solidification microstructure with (MGBs) and (SGBs) respectively and interdendritic microstructure observed in weld zone center. Weldment mechanical and microstructure examination indicated the ability to produce like this dissimilar joint with requirement of design criteria and indicated that the failure in like this joint excepted to be in low alloy steel side. The result and microstructure analyses of this research is very important to understanding the variation in welding zone and HAZ microstructure and its impact in weldment mechanical properties and establish the base to produced best welding procedure according to welding zone microstructure properties.